«Ազատ եկեղեցական» աղանդի հակականոնական գաղափարախօսութիւնը 1920-ական թուականներին. քաղաքագիտական վերլուծութիւն - Յարութիւնեան, Աւագ Ա. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Секта «Вольное церковное братство» была рождением советской атеистической действительности 1920-х годов. Это был послушный инструмент советской власти, который государство использовало в борьбе с Армянской Апостольской Церковью. Раскольнической деятельностью этого движения полностью руководили органы государственной безопасности. Это движение необоснованно критиковало руководство Церкви, требовало отмены безбрачия, коренной трансформации канонического вероучения Церкви. Движение было полностью лояльно к советской власти, они даже оправдывали репрессии против Церкви. Движение «Свободная церковь» было особенно антиканоническим и вызывало разногласия в Армянской епархии Грузии. Статьи и брошюры деятелей «Свободной церкви» не имеют абсолютно никакой ценности с политической и религиозной точки зрения. Они не оставили прочного идеологического следа в реформаторском и антицерковном движении. The sect called «Free Church Brotherhood» was generated by the Soviet atheistic reality of the 1920s. It was an obedient instrument of the Soviet authorities, which the state used in the struggle against the Armenian Apostolic Church. The divisive activities of that movement were completely directed by the state security agencies. This movement unreasonably criticized the leadership of the Church, demanded the abolition of celibacy, a radical transformation of the canonical creed of the Church. The movement was completely loyal to the Soviet authorities: they even justified the repression against the Church. The “Free Church” movement was particularly anti-canonical and divisive in the Armenian Diocese of Georgia. The articles and pamphlets of “Free Church Brotherhood” members had absolutely no value from a political and religious point of view. They left no lasting ideological trace in the reformist and anti-ecclesiastical movement.
Keywords: Կրօն